Portal educativo de apoio ao cuidado a pessoas com estomia - Silva, Rudnei Prusch da (Universidade do Vale do Rio dos Sinos, 2018)
People with stomies are supported by public policies that guide the service to the user. However, the policies, which aim at the dispensing of materials and the formation of teams, do not provide tools directed to this type of service. Thus, the objective of this study was to develop an educational portal to support the care of people with stoma. The pertinence of the guidelines was established based on the performance of the researcher involving his daily routine as a nurse stomaterapist. For its design development, the following steps were followed: needs analysis; identification of users; organization of content; construction; maintenance of the educational portal. The theoretical framework was supported by the search for national and international studies published in the last five years. In the portal, materials of didactic support were made available to health professionals, especially to nursing professionals who work in the care of patients with stomies. The benefits of this study are based on the elaboration of free educational material. Therefore, the products of this study consist of an Educational Portal to Support the Care of People with Stoma which has its own domain <http://peapee.com.br>, as well as the creation of the brand “PEAPEE”.
Keywords: Estomia; Ostoma; Estomaterapeuta; Portal Educativo; Pessoas com Estomia; Estomy; Ostoma; Stomatologist; Educational Portal; People with Stoma; ACCNPQ::Ciências da Saúde::Enfermagem